Countable hyperbolic systems in the theory of nonlinear oscillations - Firman, T.I. (Carpathian Mathematical Publications, 2016)
In this article a model example of a mixed problem for a fourth-order differential equation reduced to initial-boundary value problem for countable hyperbolic system of first order coherent differential equations.